Non-Radiation-Related Osteonecrosis of the Jaws in Dogs: 14 Cases (1996–2014) - Peralta, Santiago; Arzi, Boaz; Nemec, Ana; Lommer, Milinda J.; Verstraete, Frank J. M. (Frontiers in Veterinary Science, 2015)
Osteonecrosis of the jaws is an entity of major clinical impact characterized by chronically exposed necrotic mandibular or maxillary bone. Its clinicopathological characteristics and possible inciting or risk factors are well described in humans but only anecdotally reported in dogs. Treatment modalities and outcome vary depending on the inciting factors involved and the extent and severity of the lesions. The objectives of this study were to retrospectively describe the clinicopathological features of non-radiation related osteonecrosis of the jaws in a series of 14 dogs, identify possible inciting or risk factors, and report on the surgical treatment and outcome. For all patients, the medical records were used to collect information regarding signalment, clinical signs, characteristics of the oral, jaw and dental lesions, diagnostic imaging findings, histopathological and microbiological analysis, treatment performed and outcome. The data collected showed that non-radiation related osteonecrosis of the jaws appears to be an infrequent clinical entity but of significant impact in dogs; that a history of systemic antibiotics and dental disease is common among affected dogs; that previous dental extractions are commonly associated with ONJ sites; that using a systematic diagnostic approach is essential for diagnosis; and that thorough surgical débridement combined with a course of oral antibiotics was effective in the described dogs affected by advanced non-radiation related osteonecrosis of the jaws.